Effect of Miana Leaf Extract (Plectranthus scutellarioides (L.) R.Br.) as a Natural Fungicide against Colletotrichum capsici on Chili Plants - Khoirunisa, Sally; Windiyani, Intan Poespita; Yulianty, Yulianty (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Anthracnose disease caused by the fungus Colletotrichum capsici causes rotting of ripe chili fruits and causes a decrease in chili production up to 80%. Excessive use of synthetic pesticides can cause problems for humans and the environment. Therefore, as an alternative, natural/vegetable pesticides that are more environmentally friendly can be used. Miana leaves contain flavonoids, tannins, saponins and steroid compounds that are known to be responsible for pesticide effects on plants. The purpose of this study was to determine the effectiveness of miana leaf extract as a natural fungicide and the best concentration in inhibiting the growth and development of Colletotrichum capsici fungus that causes anthracnose disease of chili plants (Capsicum annuum L.). The research method used a completely randomized design (CRD). The treatment used in the study was the concentration of miana leaf extract. The treatment used 5 concentrations of miana leaf extract (Plectranthus scutellarioides L.), namely: 0%, 5%, 10%, and 15% and 20%. Each treatment was repeated 5 times. The parameters observed were the intensity of C. capsici fungus attack, plant height, plant wet weight, and plant dry weight. The results showed that the application of miana leaf extract (Plectranthus scutellarioides L.) had no effect on each parameter, namely the intensity of C.capsici fungal attack, plant height, plant wet weight, and plant dry weight.